2018
DOI: 10.1136/jnnp-2018-319578
|View full text |Cite
|
Sign up to set email alerts
|

Muscle MRI in a large cohort of patients with oculopharyngeal muscular dystrophy

Abstract: Background and objectiveOculopharyngeal muscular dystrophy (OPMD) is a genetic disorder caused by an abnormal expansion of GCN triplets within the PABPN1 gene. Previous descriptions have focused on lower limb muscles in small cohorts of patients with OPMD, but larger imaging studies have not been performed. Previous imaging studies have been too small to be able to correlate imaging findings to genetic and clinical data.MethodsWe present cross-sectional, T1-weighted muscle MRI and CT-scan data from 168 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 41 publications
5
26
2
Order By: Relevance
“…The hierarchical clustering of patients and muscles generated according to the scores given to the single muscles (Fig. 3) confirmed that the degree of heterogeneity was higher than that observed in other muscular dystrophies [32,33] but still a trend of susceptibility or resistance to pathology could be identified for most of the muscles.…”
Section: Resultssupporting
confidence: 58%
“…The hierarchical clustering of patients and muscles generated according to the scores given to the single muscles (Fig. 3) confirmed that the degree of heterogeneity was higher than that observed in other muscular dystrophies [32,33] but still a trend of susceptibility or resistance to pathology could be identified for most of the muscles.…”
Section: Resultssupporting
confidence: 58%
“…In our case, muscle MRI and an extensive ultrasound examination led us to suspect OPMD. Regarding muscle selectivity, previous studies revealed that tongue, hamstring, and calf muscles were mainly affected in patients with OPMD with a short expansion of GCN, which contrasts with the quadriceps-dominant pattern seen in inclusion body myositis [ 6 , 7 ]. We confirmed that OPMD patients with point mutation also exhibited the same pattern of muscle impairment as those with repeat expansion.…”
Section: Discussionmentioning
confidence: 99%
“…OPMD with PABPN1 mutation is distributed worldwide, and some cases have also been reported in East Asians [ 1 5 ]. Muscle MRI studies have revealed that a pattern of tongue, hamstring, and calf muscle involvement could be considered characteristic of OPMD [ 6 , 7 ]. In 2005, Robinson and colleagues were the first to report that OPMD was caused by a c.35G > C point mutation in the PABPN1 gene, which resulted in p.Gly12Ala amino acid substitution and an increase in the number of contiguous polyalanine codons mimicking the PABPN1 triplet repeat effect [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here we have confirmed these previous results, but we have also found a good correlation between fat replacement and results of respiratory muscle function tests. It has been previously shown that the degree of fat replacement in a muscle correlates with results of specific function tests including assessment of muscle strength using handheld dynamometry or even assessment of muscle performance using timed tests such as the 6-min walking test (18)(19)(20). Accordingly, it is not surprising that fat replacement of the diaphragm or of the accessory respiratory muscles, such as thoracic muscles, has a good correlation with FVC.…”
Section: Discussionmentioning
confidence: 99%